SCIENTIFIC AND METHODOLOGICAL BASES OF MILITARY-PATRIOTIC EDUCATION OF HIGH SCHOOL STUDENTS UNDER MARTIAL LAW - Kanishevska, Liubov (Theoretical and Methodical Problems of Children and Youth Education, 2023)
The article substantiates the scientific and methodological foundations of military-patriotic education of high school students under martial law; clarifies the essence of the key concepts of the study. The purpose is to substantiate the scientific and methodological foundations of military-patriotic education of high school students of general secondary education institutions. The objectives of the study are: to clarify the essence of the key concepts of the study; to develop a structural and functional model of military-patriotic education of high school students of general secondary education institutions. In order to achieve the goal and objectives, the following theoretical methods were used: analysis, classification, generalisation, study of regulatory documents to clarify the key concepts of the study; systematization and generalization of theoretical and empirical data to develop organisational and pedagogical conditions for military-patriotic education of high school students; theoretical modelling to develop a structural and functional model of military-patriotic education of high school students of general secondary education institutions.. The approaches, principles, organisational and pedagogical conditions are defined, forms and methods of military-patriotic education of high school students are revealed; ways to improve the effectiveness of military-patriotic education of high school students of general secondary education institutions are outlined. A structural and functional model of military-patriotic education of high school students of general secondary education institutions has been developed, which contains the following blocks: target (purpose and tasks of military-patriotic education of high school students); conceptual (methodological approaches, principles of military-patriotic education of high school students); diagnostic (criteria, indicators, levels of military-patriotic education of high school students); procedural (forms, methods, organisational and pedagogical conditions; ways to improve the effectiveness of military-patriotic education of high school students). The conducted research does not exhaust all aspects of the multifaceted theoretical and practical search for a solution to the problem of military-patriotic education of high school students under martial law. The following issues require further study and development: studying the state of readiness of high school students for military service and defence of Ukraine; improving the effectiveness of postgraduate education of teaching staff on this issue.